Pengaruh ukuran perusahaan, pertumbuhan penjualan, dan komite audit terhadap tax avoidance - Sinambela, Tongam (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This research aims to determine and analyze the effect of firm size, sales growth, and audit committee on tax avoidance. The study was conducted on Resource Sector Companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The research method is descriptive quantitative, while the sampling method uses purposive sampling. The sample in the research is 12 companies. The data analysis tool used is Statistical Product and Service Solutions (SPSS) version 25. The results of the study show that company size has no significant effect on tax avoidance, sales growth has a positive and significant impact on tax avoidance, the audit committee does not affect tax avoidance, while collectively -the exact size of the company, sales growth, and the audit committee simultaneously affect tax avoidance.